Development of an Identity with a Tendency to Shame: A look from E. Erikson’s Theory and Family Interactions - Donoso Niemeyer, Tania (Revista de Psicología, 1999)
This work is an attempt to relate the resolution of the E.Erikson’s stages of psychosocial development: Autonomy versus Shame and Doubt an Initiative versus Guilt, with the development of a Healthy Identity or a Shame-Prone Identity (a concept developed by Harper & Hoopes, 1990). Some family interactional processes that facilitate the development of a Shame-Prone Identity in human beings, as well as some elements of family functioning that permit the development of a Healthy Identity are discussed next. Finally the function of the Differentiation of self process in the developmental change from a Shame-Prone Identity to a Healthy Identity is analysed.